Marketing Strategy of Byond By BSI Application to Increase Users Case Study of PT. Bank Syariah Indonesia KCP Astana Anyar Bandung - Rosmayati, Siti; Amelia, Riska (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Marketing strategies have been widely used by the online shop industry, this also applies to the banking world which is rarely highlighted, especially KCP banks. This study aims to determine the marketing strategy of BSI KCP Bandung Astana Anyar Company related to the Byond application and its implications for increasing users in the application. This study takes the form of descriptive qualitative research to explain the phenomenon raised comprehensively and uses literature studies as a basis for compiling arguments. This study produces the fact that the marketing strategy that is taking place at BSI KCP Bandung Astana Anyar Company is running effectively. This is represented by the increase in the number of existing users. This also has implications for the fact that the marketing strategy has been running effectively. This study recommends that in the future customer retention be involved in research. This is to determine the ability of BSI KCP Bandung Astana Anyar Company in maintaining the audience or consumers that have been successfully obtained from the marketing strategy that has been implemented.